Community Participation on Tourism Development in Parangtritis Tourism Area, Bantul Regency - Hulu, Meitolo; Baiquni, M.; Fandeli, Chafid; Wirasanti, Niken (E-Journal of Tourism, 2019)
Parangtritis tourist area is a famous tourist destination in the south of Yogyakarta. The tourist area which consists of a variety of tourist objects such as beaches, sanddune, culinary, religious and cultural tourism has a positive impact on the growth of tourist visits in ??Parangtritis tourist area. This study aims to examine the participation of local people in their contribution to the development of sustainable tourism areas. The method used in this study is descriptive qualitative by conducting primary and secondary data collection. Primary data was collected through interviews with local communities which involved in to the service industry, cultural arts groups and local government of Bantul Regency. The results of the study are (1) the local community has contributed to the development of the Parangtritis tourist area through local cultural activities, tourist attractions and providing of facilities regarding the needs of visitors. (2) the local government of Bantul Regency has several programs related to the empowerment in each of government institution that are addres service industry, tourism local groups and build facilities and infrastructure. But the contribution of local communities has not become a tourist attraction and sustainable. Empowerment programs from local governments have not been specific to training related to services and business activities that are suitable for tourism activities in ??Parangtritis tourist area. Keywords: Community participation, tourist area, sustainable tourism.